Involuntary return migration to Kosovo: Tackling challenges for successful reintegration - Judith Möllers; Diana Traikova; Thomas Herzfeld; Egzon Bajrami (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
Kosovo currently faces the challenge of reintegrating thousands of returned migrants who left the country in 2014 /2015. This migration wave was discussed in the IAMO Policy Brief 24. After facing restrictive asylum policies in the destination countries in Western Europe, more than 20,000 people returned to Kosovo in 2015 and 2016. Based on the results of an empirical survey of around 180 returnees, this policy brief discusses a number of reintegration issues. In addition to low levels of education and skills, reintegration is impeded above all by the precarious state of Kosovo's labour market. This is compounded by a psychological burden that often arises from the sometimes traumatic experience of migration and involuntary return. The migration of Kosovars is at risk of becoming a vicious cycle composed of involuntary return and problems reintegrating, resulting in a further attempt at migration. Indeed, the results of the study show that many returnees do not intend to remain in Kosovo.
urn:nbn:de:gbv:3:2-81518
Keywords: 330